Annual assessment of Echinococcus multilocularis surveillance reports submitted in 2020 in the context of Commission Delegated Regulation (EU) 2018/772 - European Food Safety Authority (EFSA); Gabriele Zancanaro (EFSA Journal, 2021)
Abstract This report is part of the Echinococcus multilocularis surveillance scientific reports which are presented annually by EFSA to the European Commission and are intended to assess the sampling strategy, data collection and detection methods used by Finland, Ireland, the UK and Norway in their respective surveillance programmes. The surveillance programmes of these four countries were evaluated by checking the information submitted by each of them and verifying that the technical requirements were fulfilled as laid down in Commission Delegated Regulation (EU) 2018/772 of 21 November 2017 supplementing Regulation (EU) No 576/2013 of the European Parliament and of the Council with regard to preventive health measures for the control of E. multilocularis infection in dogs, and repealing Delegated Regulation (EU) No 1152/2011. Due to the UK exiting the European Union and under the Withdrawal Act, the data submitted by the UK after the 31 January 2020 are excluded from this assessment. The information was divided in four different categories for assessment: the type and sensitivity of the detection method, the selection of the target population, the sampling strategy and the methodology. For each category, the main aspects that need to be considered in order to accomplish the technical requirements of the legislation were checked against compliance of several criteria. All the countries participating in this surveillance (Finland, the UK, Ireland and Norway) succeeded in the fulfilment of the technical legal requirements foreseen in Commission Delegated Regulation (EU) 2018/772 concerning these four different categories. Within the UK, Northern Ireland fulfils those requirements only when assuming a diagnostic test sensitivity value of 0.99, provided by the national reference laboratory, which is higher than the sensitivity value suggested by EFSA (conservative value of 0.78) and not supported by adequate scientific evidence. None of the four countries recorded positive samples in the 12‐month reporting period.